The Power of Instagram ‘Like’ - Sophie Ariella Tanujaya (Kata Kita: Journal of Language, Literature, and Teaching, 2022)
This study aims to find out how Instagram ‘Likes’ affect its receivers. The source of the data is in-depth interviews with four informants, two from each gender. The informants come from the age group of 18— 24 because adolescents born in the late 1990s or early 2000s grew up with the emergence of social media; thus. Coincidentally, people from the aforementioned age group are also the most susceptible to mental health issues. The author implemented ethnography in data collection and analyzed it using Cooley’s ‘looking-glass self’ theories. The findings reveal that Instagram ‘Likes’ have subliminal power over the receivers through the means of self-perception, interpersonal relations, and follow-up actions.Keywords: Instagram Like, Power relation, Looking-glass Self; Social media, Instagram